INTRODUCTION OF MONAKSARA (MONOPOLI BAHASA DAN KEBUDAYAAN NUSANTARA) AS A PROTOTYPE OF BIPA LEARNING MEDIA AT UIN RADEN MAS SAID SURAKARTA - Siti Isnaniah; Afrizal Mufti (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
Globalization has increased cross-cultural communication needs and stimulated growing interest in Indonesian as a foreign language (BIPA). At beginner levels (B1–B2), speaking often stalls due to limited vocabulary, cognitive load, and social anxiety; thus, media that link communicative functions with authentic cultural contexts are needed. This article introduces MONAKSARA (Monopoly of Indonesian Language and Culture) as a prototype board-game medium for BIPA classes at UIN Raden Mas Said Surakarta. We adopt a prototype development approach with Define–Design–Develop stages: document-based needs analysis (B1–B2 syllabus and textbooks), mapping of game mechanics to communicative functions, and prototype construction. The outcome is a culturally themed board (food, heritage sites, places of worship, ceremonies) and “speaking-chance” cards providing scaffolded key expressions. The design is aligned with TBLT and the output/interaction hypotheses, game-based learning principles, cognitive-load management, and sociopragmatic competence. Anticipated strengths include engagement, equitable turn-taking, and language–culture integration; limitations include facilitator dependency, potential overload with lengthy instructions, and online-mode adaptation needs. This article does not report effectiveness testing; a staged evaluation (expert review, small-scale pilot, pre–post speaking tasks) is proposed to validate conceptual feasibility and pedagogic impact.